2023
DOI: 10.1002/cey2.373
|View full text |Cite
|
Sign up to set email alerts
|

Insights on advanced substrates for controllable fabrication of photoanodes toward efficient and stable photoelectrochemical water splitting

Abstract: Conversion of solar energy into H2 by photoelectrochemical (PEC) water splitting is recognized as an ideal way to address the growing energy crisis and environmental issues. In a typical PEC cell, the construction of photoanodes is crucial to guarantee the high efficiency and stability of PEC reactions, which fundamentally rely on rationally designed semiconductors (as the active materials) and substrates (as the current collectors). In this review work, we start with a brief introduction of the roles of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 295 publications
0
16
0
Order By: Relevance
“…Although electrical contact optimization is beyond the scope of the present work, integration of electron-selective contacts or interfacial TCOs for improved majority carrier extraction may provide a viable route to improving PEC performance characteristics. A recent review on the substrate choice for photoanodes can be found in Hou et al 42 To further investigate the stabilities of all samples, CA measurements were performed under constant illumination and an applied bias of 1.23 V vs RHE (Figure S7). Although these measurements confirm that the oxynitride films are more stable than the pure nitride films, all samples undergo degradation under sustained operation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although electrical contact optimization is beyond the scope of the present work, integration of electron-selective contacts or interfacial TCOs for improved majority carrier extraction may provide a viable route to improving PEC performance characteristics. A recent review on the substrate choice for photoanodes can be found in Hou et al 42 To further investigate the stabilities of all samples, CA measurements were performed under constant illumination and an applied bias of 1.23 V vs RHE (Figure S7). Although these measurements confirm that the oxynitride films are more stable than the pure nitride films, all samples undergo degradation under sustained operation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, using a suitable conductive scaffold and/or a hole transport layer in a photoanode can further enhance the charge transport and separation efficiency. 40,41 The introduction of oxygen vacancies in metal oxides is also effective in improving the PEC performance. 42 In addition to the mentioned approaches, decoration of metal oxides with functional materials like organic polymers and metal-organic frameworks (MOFs) can equally facilitate the charge transport and separation.…”
Section: Overview Of Strategies To Improve Pec Water Splitting Effici...mentioning
confidence: 99%
“…A significant number of new generation photocatalysts, including graphitic carbon nitrides, conjugated polymers, metal–organic frameworks (MOFs), covalent organic frameworks (COFs), boron nitride-based and MXene, etc. have also emerged. Specifically, polypyrrole (PPy) nanostructures possess a narrow bandgap, which enables higher visible light harvesting, and extensive π-cloud delocalization renders higher electrical conductivity that facilitates greater charge separation and transfer, which makes them ideal for photocatalytic water splitting. …”
Section: Introductionmentioning
confidence: 99%